KONGHUCU DI KOREA KONTEMPORER DAN SUMBANGANNYA TERHADAP KERUKUNAN UMAT BERAGAMA DI INDONESIA - Anna, Dian Nur (Jurnal Ilmu Ushuluddin, 2013)
Confucianism is a minority religion in Korea and Indonesia, but the spiritual movement of Confucianism can be accepted by some religions and may also be practiced. This study aimed to uncover how did Koh Byong-ik on Confucianism in South Korea in the future and how was this contemporary contribution to religious harmony in Indonesia critical analysis. Results of this study indicated that a statistically Confucian minority turned out after a deep study, a dominating ideology Korea. Though a minority, they had the spiritual strength to embrace a religion. The Confucian doctrine turned out to support the harmony of religious life and this was the initial capital to strengthen brotherhood among religions.